An expanded reference map of the human gut microbiome reveals hundreds of previously unknown species - Sigal Leviatan; Saar Shoer; Daphna Rothschild; Maria Gorodetski; Eran Segal (Nature Communications, 2022)
Here, Leviatan et al. produce 241,118 genome assemblies to produce a new human gut microbiome reference set of 3,594 species genomes, of which 310 represent previously undescribed species, making the catalog a valuable resource for further research.